Using Cellulose Nanocrystal as Adjuvant to Improve the Dispersion Ability of Multilayer Graphene in Aqueous Suspension - Zhang, Haiqiao; Wu, Yan; Yang, Feng; Dong, Huiling; Bian, Yuqing; Jia, Huanliang; Xie, Xuqin; Zhang, Jilei (Frontiers in Bioengineering and Biotechnology, 2021)
Cellulose nanocrystal (CNC) has been applied in various fields due to its nano-structure, high aspect ratio, specific surface area and modulus, and abundant of hydroxy groups. In this work, CNC suspensions with different concentrations (0.4%, 0.6%, and 0.8%) were used as the adjuvant to improve the dispersion ability of multilayer graphene (MLG) in aqueous suspension, which is easy to be aggregated by van der Waals force between layers. In addition, N-methyl-2-pyrrolidone (NMP) and ethanol, and ultrapure water were used as control groups. Results from Transmission electron microscopy, Fourier Transform Infrared Spectroscopy, and absorbance showed that MLG had a better dispersion performance in the CNC suspensions, comparing to the other solutions. The Raman spectrum analysis showed that the mixtures of 1.0 wt% MLG with 0.4% CNC had the least defects and fewer layers of multilayer graphene. In addition, it is found that CNC suspension with 0.8% concentration showed the highest ability to disperse 1.0 wt% MLG with the most stable performance in suspension. Overall, this work proved that the potential application of CNC as the adjuvant in the field of graphene nanomaterials.